Investigating the Structural and Magnetic Properties of Nickel Oxide Nanoparticles Prepared by Precipitation Method - hadi, karrar; M. Al- Saadi , Tagreed (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2022)
This work used the deposition method to synthesize nickel oxide nanoparticles. The materials mainly used in this study were nickel sulfate hexahydrate (as a precursor) and NaOH (as a precipitant). The properties of the nanopowder were characterized by XRD, FE-SEM, EDX, and VSM. The obtained results confirmed the presence of nickel oxide nanoparticles with a face-centered cubic (FCC) structure with a lattice constant (a=4.17834 Å). Scherer and Williamson-Hall equations were used to calculate the crystallite size of about (30.5-35.5) nm. The FE-SEM images showed that the particle shape had a ball-like appearance with a uniform and homogeneous distribution and confirmed that the particles were within the nanoscale. The presence of oxygen and nickel atoms was confirmed by the EDX test. The magnetic properties results showed that nanoNiO had a narrow hysteretic loop. It consumed the least amount of energy and, therefore, can be used as a core for electric motors and transformers.